2012
DOI: 10.1093/qjmed/hcs123
|View full text |Cite
|
Sign up to set email alerts
|

The long-term predictive value of the neutrophil-to-lymphocyte ratio in Type 2 diabetic patients presenting with acute myocardial infarction

Abstract: Increased NLR post-AMI is an independent predictor of major adverse cardiac events in diabetics. Monitoring this easily obtainable new index allows prognostication and risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 47 publications
(54 reference statements)
1
48
1
1
Order By: Relevance
“…Regarding this last aspect, the literature data seem to be contrasting; in fact, while some authors found a difference in NLR in relation to the diabetic disease [5,29,35], others did not point out this trend [13,22,24,27,43]. In our small survey this ratio differentiates smokers and non smokers and this datum seems to agree with the findings of several authors [5,13,22,35], but it is different from which observed by others [24,27,43].…”
Section: Conclusive Considerationscontrasting
confidence: 82%
See 1 more Smart Citation
“…Regarding this last aspect, the literature data seem to be contrasting; in fact, while some authors found a difference in NLR in relation to the diabetic disease [5,29,35], others did not point out this trend [13,22,24,27,43]. In our small survey this ratio differentiates smokers and non smokers and this datum seems to agree with the findings of several authors [5,13,22,35], but it is different from which observed by others [24,27,43].…”
Section: Conclusive Considerationscontrasting
confidence: 82%
“…The average NLR results the best predictor of short-and long-term survival compared to other leukocyte parameters, such as neutrophil or lymphocyte count [5], probably because this ratio is less altered by other conditions, such as dehydration or over-hydration [4]. Lee et al have demonstrated that the NLR value at the admission is an independent predictor of 1-year reinfarction and mortality in diabetic subjects with AMI [29].…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[16][17][18] During systemic inflammation, the release of cytokines, such as IL-1ra, IL-6, IL-7, IL-8, IL-12 and platelet derived growth factor (PDGF), is followed by neutrophil activation and elevation of NLR. NLR is a more stable measure than the individual neutrophil and lymphocyte counts, and is less affected by conditions which change the individual cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…One major difficulty in using NLR value as a prognosticator in disease processes is determining an appropriate cut-off value around which disease outcomes differ. The appropriate NLR cut-off value is likely to change with the stage of illness, laboratory techniques employed, concomitant infection and patient demographic characteristics (26). In our study, a statistically significant difference in all-cause mortality was found between patients using the cutoff value of 3.…”
Section: Discussionmentioning
confidence: 63%